2013
DOI: 10.1371/journal.pone.0077985
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Microorganisms and Enzymes Involved in High-Solids Decomposition of Rice Straw Using Metagenomic Analyses

Abstract: High-solids incubations were performed to enrich for microbial communities and enzymes that decompose rice straw under mesophilic (35°C) and thermophilic (55°C) conditions. Thermophilic enrichments yielded a community that was 7.5 times more metabolically active on rice straw than mesophilic enrichments. Extracted xylanase and endoglucanse activities were also 2.6 and 13.4 times greater, respectively, for thermophilic enrichments. Metagenome sequencing was performed on enriched communities to determine communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 56 publications
3
51
2
1
Order By: Relevance
“…Thus, engineered culture conditions are used to enrich for desirable traits and lead to the discovery of functional microbial consortia or specific microorganisms. For example, starting with microbial communities collected from compost and soil environments, a selection of simplified communities have been found that can deconstruct lignocellulosic biomass in extreme conditions, such as high temperature, high-solid loading, and low moisture (DeAngelis et al 2010;Jimenez et al 2014;Reddy et al 2013;Simmons et al 2014;Yu et al 2015). The enrichment process generates less complex lignocellulolytic microbial communities that can facilitate targeted discovery of potential enzymes and microorganisms for biomass deconstruction .…”
Section: Discovering and Screening For Il Tolerant Microorganisms Relmentioning
confidence: 99%
“…Thus, engineered culture conditions are used to enrich for desirable traits and lead to the discovery of functional microbial consortia or specific microorganisms. For example, starting with microbial communities collected from compost and soil environments, a selection of simplified communities have been found that can deconstruct lignocellulosic biomass in extreme conditions, such as high temperature, high-solid loading, and low moisture (DeAngelis et al 2010;Jimenez et al 2014;Reddy et al 2013;Simmons et al 2014;Yu et al 2015). The enrichment process generates less complex lignocellulolytic microbial communities that can facilitate targeted discovery of potential enzymes and microorganisms for biomass deconstruction .…”
Section: Discovering and Screening For Il Tolerant Microorganisms Relmentioning
confidence: 99%
“…But due to the single point analysis, the succession of microorganisms that had occurred during the enrichment period remains unknown. It is interesting to note, however, that in spite of the different incubation times in the present versus previous studies, some major features are similar: a high accumulation of Actinobacteria in compost-like enrichments or a higher proportion of Firmicutes and Chloroflexi , with a lower abundance of Gemmatimodadetes and Trueperaceae and nearly no Actinobacteria in a thermophilic liquid enrichment [9,10,14,30]. …”
Section: Discussionmentioning
confidence: 43%
“…The cumulative carbon dioxide evolution rate (cCER) decreased as the IL concentration increased (Table 1) (14). The cCER seen with switchgrass amended with 2% IL was significantly lower than the cCER from samples amended with 0% and 0.5% IL.…”
Section: Resultsmentioning
confidence: 99%
“…Incubations were conducted as described previously (14, 24). In summary, switchgrass was wetted with minimal media (25) to a moisture content of 400% (wt) dry basis (g water [g dry solid] −1 ), inoculated with 10% (wt) inoculum (g dry inoculum [g dry solid] −1 ), and then amended with IL.…”
Section: Methodsmentioning
confidence: 99%